Recommendations for participation in competitive sports of athletes with arterial hypertension: a position statement from the sports cardiology section of the European Association of Preventive Cardiology (EAPC). (24th August 2018) - Niebauer, Josef; Börjesson, Mats; Carre, Francois; Caselli, Stefano; Palatini, Paolo; Quattrini, Filippo; Serratosa, Luis; Adami, Paolo Emilio; Biffi, Alessandro; Pressler, Axel; Schmied, Christian; van Buuren, Frank; et al.
Abstract: Current guidelines of the European Society of Cardiology advocate regular physical activity as a Class IA recommendation for the prevention and treatment of cardiovascular disease. Despite its undisputed multitude of beneficial effects, competitive athletes with arterial hypertension may be exposed to an increased risk of cardiovascular events. This document is an update of the 2005 recommendations and will give guidance to physicians who have to decide on the risk of an athlete during sport participation.